Perlindungan Hak Kekayaan Intelektual Tentang Merek - Wulandari, Dewi; Ahmad, Muhammad Al Habsy (Jurnal Litigasi Amsir, 2023)
This research aims to find out how public legal awareness is regarding the protection of intellectual property rights regarding brands in West Sulawesi and what factors influence the low level of public legal awareness regarding the importance of protecting brand rights in West Sulawesi. The research used was empirical, conducted at the regional office of the Ministry of Law and Human Rights. The results of this research indicate that public legal awareness regarding the protection of intellectual property rights regarding brands in West Sulawesi based on data obtained from the regional office of the Ministry of Law and Human Rights, as well as interviews conducted with staff in the intellectual property sub-sector, is considered to be still low due to the large number of goods/services being produced. have not registered in intellectual property and the factors that influence the low level of trademark registration are caused by legal factors, legal means and facilities, community factors and cultural factors.